Aging Society, Loneliness And Social Support: Is Social Media Making Them Less Lonely? - Shamugam, Lalitha (2015)
National Statistics Department (NSD) of Malaysia reported, by 2021 Malaysia’s population aged 65 years and over will reach 7.1 % of the total population and based on United Nations (UN), Malaysia is an aging society in the same year. The steady increase in this aging population generates new challenges, resulting Malaysia to adopt active ageing policy framework to optimize opportunities for social and mental wellbeing, in order to promote good quality of life as people age (United Nations, 2007). Previous studies show that acute loneliness can impact gravely on wellbeing and quality of life, with demonstrable negative health effects (Greaves, 2006; Pitkala, 2009). Aging people are particularly vulnerable for social isolation and loneliness even though it can affect everyone. With advancing age, it is inevitable that people lose connection with their friendship networks and that they find it more difficult to initiate and belong to a new friendship networks. The development of new media, especially social media has made people connected or access information ubiquitously in order for them to be less lonely. The primary objective in this research is to examine the relationships between social media usage, social support, and loneliness among aging society in Malaysia. Second, to identify the socio-demographics difference with respect to social media usage, social support, and loneliness. In this research, we will incorporate mixed methods, for qualitative approach we will conduct focus group interviews with older adults in Malaysia in order to understand attitudes towards social media and how they communicate with members of their social network given the presence of social media. Meanwhile, for quantitative approach we will use UCLA Loneliness Scale and Perceived Social Support Questionnaire (Procidano, 1983) to measure the level of loneliness and social support for this research sample.